2017
DOI: 10.1111/jan.13363
|View full text |Cite
|
Sign up to set email alerts
|

The embodied nurse: Interdisciplinary knowledge exchange between compassionate nursing and recent developments in embodied leadership studies

Abstract: The results suggest common ground between nursing and contemporary leadership research in the exposition of behaviours; namely, being non-judgmental, listening actively, reflective practice and embracing uncertainty. Several implications can therefore be expected through the exchange of knowledge resulting from collaboration between researchers in the two disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 117 publications
1
8
0
Order By: Relevance
“…hypothesis is consistent with reports from other health care professions (Bonvicini et al, 2009;Epstein, Campbell, Cohen-Cole, Whinney, & Smilkstein, 1993;Koya, Anderson, & Sice, 2017;Leach, 2005). Several studies in the health care industry have reported a relationship between care described as "empathetic" or "compassionate" and improved treatment outcomes, reduced risk of professional litigation, improved patient adherence to medical protocols, and greater likelihood that patients will share qualitative assessment information (Bonvicini et al, 2009;Epstein et al, 1993;Koya et al, 2017;Leach, 2005). The establishment of these therapeutic relationship skills can also directly influence practitioners themselves.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…hypothesis is consistent with reports from other health care professions (Bonvicini et al, 2009;Epstein, Campbell, Cohen-Cole, Whinney, & Smilkstein, 1993;Koya, Anderson, & Sice, 2017;Leach, 2005). Several studies in the health care industry have reported a relationship between care described as "empathetic" or "compassionate" and improved treatment outcomes, reduced risk of professional litigation, improved patient adherence to medical protocols, and greater likelihood that patients will share qualitative assessment information (Bonvicini et al, 2009;Epstein et al, 1993;Koya et al, 2017;Leach, 2005). The establishment of these therapeutic relationship skills can also directly influence practitioners themselves.…”
supporting
confidence: 91%
“…The establishment of these therapeutic relationship skills can also directly influence practitioners themselves. For example, Koya et al (2017) suggested that nurses who establish therapeutic alliances with their patients may have less stress and improved work performance, including making better strategic decisions..…”
mentioning
confidence: 99%
“… 51 , 60 , 65 , 66 , 71 , 74 , 76 , 79 , 80 , 84 A number of the studies specifically highlighted the importance of managing change and assisting others in this regard 53 , 58 , 59 , 61 , 67 , 68 , 79 , 80 , 85 as well as practicing in an ethically responsive manner. 47 , 60 , 62 , 74 , 79 , 84 Some studies did not specify the leadership skills, but merely reported on broad or general leadership skills, 50 , 54 , 61 , 63 , 64 , 70 , 73 , 75 , 83 , 86 while other studies were more specific and mentioned, for example, clinical leadership, 49 adaptive leadership, 72 authentic leadership, 74 collaborative leadership, 12 , 78 personal leadership, 65 or in some cases, not leadership skills but management skills. 59 , 60 , 63 , 64 , 68 , 78–81 , 87 …”
Section: Resultsmentioning
confidence: 99%
“… 51 , 52 The nature of the skills which were addressed in the different studies varied greatly and hence resulted in different types of skills such as IPC or teamwork skills that improved in 18 studies, 50 , 52 , 53 , 55 , 58 , 60 , 61 , 65 , 75–79 , 81–84 followed by 15 studies that emphasized communication skills, 12 , 50 , 52 , 55 , 57 , 58 , 60 , 61 , 63 , 68 , 73 , 77 , 81 , 82 , 85 and increased self-awareness/self-identity and self-confidence in 10 studies. 59 , 60 , 62 , 64 , 71 , 74 , 75 , 77 , 79 , 84 Four studies each reported back on improved skills related to conflict resolution, 55 , 58 , 61 , 63 patient care, 48 , 65 , 83 , 84 and motivating others, 53 , 58 , 62 , 85 while three studies each reported on skills related to coping with change, 53 , 61 , 80 and problem-solving. 61 , 72 , 85 From Table 4 , it is possible to see that any combination of outcomes was possiblefor example, improving both knowledge and skills, or improving skills and facilitating a positive attitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation